Change of School Organizations - Secondra Hudaya; Kristianus Riberu (Faculty of Education Universitas Negeri Malang, 2021)
the purpose of this study is to describe organizational changes, changes in school organizations and the meaning of changes in school organizations. This study uses a literature review study method with content analytic analysis techniques. The results of the analysis show that schools have three basic links, namely: Input - transformation process - output - (outcome). The internal and external environments that affect the three basic links are also connected. Changes in school organization are caused by government intervention, societal values, technological and scientific developments, administrative processes and meeting the needs of employees. Schools cannot resist change. Any change in its form makes the school organization more adaptive, manages change, empowers internal and external potential so that school excellence becomes the aspiration of the institution.